Design of Dodol Mixer on Based on Microcontroller Arduino Nano - Saputra, Chindra; Sutoyo, Mochammad Arief Hermawan; Bustami, M. Irwan; Kibianty, Desi; Kustiansyah, Anggy (Journal of Applied Business and Technology, 2024)
In the process of cooking dodol dough requires the power of several people to continuously stir until the dough releases air bubbles. the process of making dodol generally takes time depending on how much dough you want to cook. If you want to cook 10 kg of dodol dough, then the time needed to cook it is approximately 8-10 hours with normal or medium heat. Currently, the household-scale dodol industry still uses the manual method for the dodol mixing process, which will require energy. more than one person to stir for a long time so that it will take time for one repetitive job and the production costs will be higher. With this tool, it is hoped that the household-scale dodol industry will become more efficient, because there is no need to manually stir and can do another work while the dodol dough is being stirred.